(untitled) (Revista de Pesquisa: Cuidado é Fundamental, 2021)
Objective: to analyze the conception of elderly people in groups of coexistence. Methods: descriptive, exploratory, qualitative approach, with 16 elderly people attending groups of coexistence. The information was collected through the use of the focal group technique. The data were analyzed and organized from the Thematic Content Analysis technique. Results: the vision about living groups was related to the creation of ties and relational ties, as a space capable of promoting health, well-being and quality of life, besides becoming a strategy to avoid loneliness. Finally, they emphasize the importance of sharing positive feelings and experiences. Conclusion: the elderly have a varied conception of living groups, emphasized the importance of these spaces to re-signify old age and favor the resocialization of the elderly person promoting a successful and healthy aging